PERAMALAN INDEKS HARGA YANG DIBAYAR PETANI (PUPUK DAN PESTISIDA) DI PROVINSI NUSA TENGGARA BARAT MENGGUNAKAN METODE ARIMA INTERVENSI - Setiawan, Rifani Nur Sindy; Febrilia, Baiq Rika Ayu; Kusuma, Wirajaya (JURNAL AGRIMANSION, 2023)
The level of farmer welfare can be measured through the Farmer’s Terms of Trade (FTT), one of the indicators used to measure it is the Price Paid by Farmers Index (IB). IB is expenditure by farmers in the form of goods or services for household consumption, production costs, and additional capital goods, while the prices of fertilizers and pesticides contribute to determining the IB value in the production cost category. Because the FTT is largely determined by the IB in the fertilizer and pesticide category, a more in-depth analysis of the development of this index value is needed so that forecasts can be made regarding the development of the IB in the fertilizer and pesticide category for the next period. The data used in this research is data on the Price Index Paid (IB) of farmers for production costs in the form of fertilizers and pesticides from January 2017 to December 2021. The research method used is ARIMA intervention because of the drastic decline in IB during the pandemic COVID. IB forecasting results for the next six months show an upward trend, and in June 2022 it will reach a price index of 120.937.